Konsep bentuk kujang sebagai salah satu identitas eksistensi budaya Sunda dalam perencanaan taman di Kota Bogor - Radnawati, Daisy; Febriani, Yusi; Nurhayati, Eli (Jurnal Arsitektur Lansekap, 2018)
Kujang form concept as an identity of Sundanese culture existence in Bogor urban park planning. City Park is a public space where people gather and do various activities in it. There are several functions of urban parks such as community associations, sports venues, environmental education, health promotion and aesthetic value. Some of the city parks in Bogor are Malabar Park, and Empang Park which is surrounded by residential areas and is mainly used as a sports vessel. Contrary to its function, the activity has not been supported by facilities that can provide user comfort and security. The problems seen in the existing condition of the park in Bogor are generally very bad and unkempt, some of the park has no recreational facilities or other supporting facilities that can be used by the public, has no strong character or identity, and has not connected between parks (connecting park). Researchers collect data through direct observation at the research site. Researchers looked at the entire site including physical aspects (accessibility, entrance, circulation path, road dimension, climatology), biophysical (vegetation and wildlife) aspects, and socio-cultural aspects (park visitor behavior). Observations are used by researchers as additional information in the study. Field survey in this research can be obtained by observation, interview and documentation. The concept of connecting park is applied to provide connectivity between parks that have an identity and can present the elements and appropriate park facilities so as to provide satisfaction, pleasure, comfort, and security to the user. Kujang as traditional weapon of Sundanese applied as the form and design concept of the parks.